Briefing: Industry 4.0 in Construction: Radical Transformation or Restricted Agendas?. Issue 4 (7th August 2020) - Chan, Paul W
Abstract : The fourth industrial revolution (Industry 4.0) is poised to transform the architecture, engineering and construction (AEC) sector from a project-based industry to a market-based industrialised process. Yet, its (s)low uptake can be attributed to current emphasis on technological adoption. In this briefing note, it is argued that ignoring non-technical aspects such as the social will to change and ethical choices can result in Industry 4.0 failing to deliver its transformative power in the AEC sector. Rather than to focus on technology, questions are raised around systemic change by considering people and process issues. Furthermore, instead of focussing on the calculative value of Industry 4.0, there is also a need to consider (ethical) values when making decisions in the data-driven world of Industry 4.0.